Online Peer Review of Oral Presentations. (December 2022) - Ho, Eric
Peer review has been promoted for decades in order to engage students in the assessment process which then leads to better learning outcomes. This teaching pedagogy is relatively innovative in the Hong Kong language classroom because English as a Second Language (ESL) students are not aware of their responsibility in the language learning process and they think that all assessment-related tasks are the teachers' sole responsibility. The focus on the language system also hinders the importance of skills. Engaging students in the assessment process is challenging. In this Innovations in Practice article, the integration and implementation of online peer review of oral presentations into an undergraduate English Literature curriculum will be presented. The aim of the integration is to bridge the gap between tertiary education and the workplace, equipping students with better oral presentation skills. The two-staged setting could encourage learners to reflect on their performance and bring the feedback forward to the next assessment. Being a reviewer and reviewee provided them with opportunities to learn from the enhanced number of exemplars and peer feedback. They could also realize the discrepancies between their own and their classmates' performances. Such realization allowed them to better understand the assessment requirements and the required skills, and then develop their own personalized plans for improvement before the actual assessment. As a result, they could learn and improve throughout the semester, both inside and outside the classroom. Involving learners in the assessment process and enhancing their assessment literacy seemed to counter-balance the dominance of content-based, summative assessment in the ESL context.